Meta-material for nuclear particle detection. (21st December 2016) - Merlo, V; Salvato, M; Lucci, M; Ottaviani, I; Cirillo, M; Scherillo, A; Schooneveld, E M; Vannozzi, A; Celentano, G; Pietropaolo, A
Abstract: Superconducting strips coated with boron were engineered with a view to subnuclear particle detection. Combining the characteristics of boron as a generator of α -particles (as a consequence of neutron absorption) and the ability of superconducting strips to act as resistive switches, it is shown that fabricated Nb–boron and NbN–boron strips represent a promising basis for implementing neutron detection devices. In particular, the superconducting transition of boron-coated NbN strips generates voltage outputs of the order of a few volts thanks to the relatively higher normal state resitivity of NbN with respect to Nb. This result, combined with the relatively high transition temperature of NbN (of the order of 16 K for the bulk material), is an appealing prospect for future developments. The coated strips are meta-devices since their constituting material does not exist in nature and it is engineered to accomplish a specific task, i.e. generate an output voltage signal upon α -particle irradiation.